MEMBANGKITKAN SIKAP NASIONALISME BAGI GENERASI MUDA MELALUI IMPLEMENTASI PENDIDIKAN NILAI-NILAI PANCASILA - Maola, Putri Sofiatul; Dewi, Dinie Anggraeni (Universitas Pakuan, 2021)
GENERATING AN ATTITUDE OF NATIONALISM FOR THE YOUNG GENERATION THROUGH THE IMPLEMENTATION OF PANCASILA VALUES EDUCATIONThe research aims to arouse an attitude of nationalism in the spirit of youth through the implementation of Pancasila values. As, Pancasila is the basis of the State which should be instilled in the soul of each individual, especially the younger generation. This research was conducted using a qualitative method through a descriptive analytic approach, in which the theory or basis of discussion was taken from the results of literature studies such as books, articles and journals. In this era of globalization, there have been many changes in the tantalizing patterns of human life in the world in terms of technology, communication and dress, so this globalization can have positive and negative impacts. As the nation's successor, we must be able to filter out the negative effects of globalization by implementing or applying Pancasila values, this can be achieved by fostering an attitude of nationalism, one of which is loving domestic products. In Pancasila, there are many noble values that reflect the nation's culture. These values are reflected in each of the precepts in Pancasila. Therefore, through the implementation of Pancasila values, it is hoped that it can become a reference for the younger generation who are the nation's successors who are still guided by Pancasila in life.